Geochronological reconsideration of the eastern European key loess section at Stayky in Ukraine - Kadereit, Annette; Wagner, Günther A. (Climate of the past, 2014)
Abstract. Event-stratigraphical correlations between regional terrestrial sedimentary archives and marine or ice-core records that provide climate history are highly desirable for a deeper understanding of the effects of global climate change. However, such correlations are not simple, as the terrestrial records tend to be floating and fragmentary, and usually show varying sedimentation rates. Therefore, a reliable chronometric framework is a prerequisite for any event stratigraphy involving terrestrial archives. We propose that the age model underlying the event-stratigraphical approach for the eastern European key loess section at Stayky in Ukraine needs revision. Here we explore why it is unlikely that the Middle Pleniglacial Vytachiv Soil developed during Greenland interstadial (GIS) 8, and why the embryonic soils in the upper part of the Upper Pleniglacial part of the loess section most likely post-date the Heinrich 2 event. As a consequence, the revised age-model challenges the earlier suggested correlation of the suite of incipient soils above the Vytachiv Soil with Greenland Interstadials, which was supposed to start with GIS7 but for which matching from after GIS5 seems more likely. The revised chronology suggests that the transition from Middle to Upper Pleniglacial environmental conditions at the eastern European key section occurred during the final phase of marine isotope stage (MIS) 3. Thus, the picture appears to be in accordance with that of the western European key section at Nussloch. This points to a common driver of palaeo-environmental change in both regions, such as early late glacial maximum (LGM) advances of the Arctic ice shield or changes of the North Atlantic circulation and sea-ice distribution associated with changes in the palaeowind field relevant to aeolian loess deposition and soil formation. To test and substantiate the alternative age model, more chronologies for well-stratified loess sections throughout the European loess belt are required.
Gesehen am 09.10.2020